Oryoki and the Oryoki chant: including the sutra of the recollection of the noble three jewels and the Tibetan monastic meal liturgy and full commentaries to them - Duff, Tony (Padma Karpo Translation Committee, 2008)
A meditative form of eating that emphasizes mindfulness awareness practice by abiding to a strict order of precise movements